Knowledge, Attitude, and Practice (KAP) toward Cervical Cancer Screening among Adama Science and Technology University Female Students, Ethiopia - Almaz Tadesse; Mesfin Tafa Segni; Hailu Fekadu Demissie (International Journal of Breast Cancer)
Background. Cervical cancer is a complication of Human Papillomavirus (HPV) infection is the second most common cancer in women worldwide. Eighty percent of the cases occur in low-resource countries. According to the 2009 World Health Organization report, the age-adjusted incidence rate of cervical cancer in Ethiopia was 35.9 per 100,000 patients with 7619 annual number of new cases and 60-81 deaths every year. The study is aimed at assessing the level of knowledge, attitude, and practice concerning cervical cancer among female students at Adama Science and Technology University. Methodology. An institutional based cross-sectional study was conducted among 667Adama Science and Technology University female students. A simple random sampling method was used to select the respondents. Structured self-administered questionnaire was used for data collection. Results. About 404 (60.6%) of the participants heard about cervical cancer, 478 (71.7%) had positive attitude towards cervical cancer screening, and only 15 (2.2%) participants were screened for cervical cancer. Lack of information about cervical cancer was the most reported reason for not attending to cervical cancer screening. Conclusion and Recommendation. The study showed that there was low knowledge on cervical cancer and screening for premalignant lesion among women. There is a need to promote and encourage women to early cervical cancer screening at precancerous stage by informing their susceptibility to cervical cancer.